Characterisation of liver pathogenesis, human immune responses and drug testing in a humanised mouse model of HCV infection. Issue 10 (6th July 2015) - Keng, Choong Tat; Sze, Ching Wooen; Zheng, Dahai; Zheng, Zhiqiang; Yong, Kylie Su Mei; Tan, Shu Qi; Ong, Jessica Jie Ying; Tan, Sue Yee; Loh, Eva; Upadya, Megha Haridas; Kuick, Chik Hong; Hotta, Hak; et al.
Abstract : Objective: HCV infection affects millions of people worldwide, and many patients develop chronic infection leading to liver cancers. For decades, the lack of a small animal model that can recapitulate HCV infection, its immunopathogenesis and disease progression has impeded the development of an effective vaccine and therapeutics. We aim to provide a humanised mouse model for the understanding of HCV-specific human immune responses and HCV-associated disease pathologies. Design: Recently, we have established human liver cells with a matched human immune system in NOD- scid Il2rg −/− (NSG) mice (HIL mice). These mice are infected with HCV by intravenous injection, and the pathologies are investigated. Results: In this study, we demonstrate that HIL mouse is capable of supporting HCV infection and can present some of the clinical symptoms found in HCV-infected patients including hepatitis, robust virus-specific human immune cell and cytokine responses as well as liver fibrosis and cirrhosis. Similar to results obtained from the analysis of patient samples, the human immune cells, particularly T cells and macrophages, play critical roles during the HCV-associated liver disease development in the HIL mice. Furthermore, our model is demonstrated to be able to reproduce the therapeutic effects of human interferon alpha 2a antiviral treatment. Conclusions: The HIL mouse provides a model for the understanding of HCV-specific human immune responses and HCV-associated disease pathologies. It could also serve as a platform for antifibrosis and immune-modulatory drug testing.